Training of application plastic waste into ecobricks at Notoprajan, Ngampilan, Yogyakarta Indonesia - Gita Indah Budiarti; Surya Adami; Erfan Fakhriyanto (Universitas Ahmad Dahlan, Yogyakarta, 2021)
Plastic waste is a serious problem in the community, especially in RW 4,5 and 6 of Notoprajan, Ngampilan, Yogyakarta. The utilization of plastic waste in the region is not yet optimal. This community service activity aims to provide education about plastic waste and train teenagers to make ecobricks. The method used is providing education about the types of plastic waste, the dangers of plastic and the various uses of plastic waste, ecobrick manufacturing. Furthermore, participants will be accompanied to practice directly making ecobricks. The results of this activity were in the form of ecobrick work by the participants. This proves that their understanding and skills have improved with this training.